Aerobic bacterial profile and antibiotic susceptibility patterns of post-operative wound infections in a tertiary care hospital - Syed Majid Ali; Jalila Qayoom; Talat Masoodi; Azhar Shafi; Arshi Syed (Medical Laboratory Journal)
Background: Post-operative wound infection has been a problem since surgery was started as a treatment modality and is the third most common cause of nosocomial infections with a reported incidence rate of 14-16%. This study aimed to investigate the prevalence, isolate and identify aerobic pathogenic bacteria from surgical site infections (SSI) and to determine the antibiotic susceptibility testing (AST) pattern of pathogenic bacteria. Methods: This study was conducted at the Department of Microbiology SKIMS-Medical College, Bemina Srinagar, over a period of six months from November 2021 to April 2022. In the study, 210 samples from patients with SSI were included. Isolation, identification, and AST of the isolates were performed by standard microbiological techniques. Results: Out of 210 SSI samples, 163 bacterial isolates were recovered and infection rate was more in 21-30 years age group (24.2%). Gram-negative bacteria were isolated in 50.4% (82/163) cases and E. coli was the most common organism (59.75%, 49/82). Gram-negative bacteria were sensitive to imipenem and none were resistant to polymyxin-B and colistin. E. coli was mostly resistant to cefoperazone, Acinetobacter and Klebsiella species were resistant to ceftazidime, Pseudomonas and Citrobacter were resistant to ceftriaxone. Gram-positive bacteria constituted 49.6% (81/163) and Methicillin-resistant Staphylococcus aureus (MRSA) was a frequently isolated species (66.6%, 54/81). MRSA- and methicillin-sensitive Staphylococcus aureus (MSSA) were mostly sensitive to amikacin, gentamycin, and tetracycline. Moreover, none of the Gram-positive isolates were resistant to linezolid, vancomycin, and teicoplanin. Enterococcus spp was mostly resistant to gentamycin. Conclusion: This study developed an insight into post-operative wound infections and their incidence, organisms’ prevalence, and their antibiogram. Culture positivity in suspected cases of SSI was high (77.6%). MRSA and E. coli were frequently isolated from Gram-positive and Gram-negative bacteria.